(untitled) (Journal of Kidney Cancer, 2023)
Intraoperative tumor thrombus embolization is a potentially lethal complication during inferior vena cava (IVC) thrombectomy for renal cell carcinoma (RCC). Intraoperative embolization is uncommonly encountered because IVC thrombectomy surgical technique is focused on avoiding this complication. Nonetheless, early recognition of embolization is essential so that emergent management can be instituted. When available, cardiopulmonary bypass (CPB) and embolectomy should be considered the gold standard for the management of intraoperative embolization. Several novel endovascular techniques are also available for selective use. We present the case of a 71-year-old female with a right renal mass and level II (retrohepatic) IVC tumor thrombus. During cytoreductive nephrectomy and IVC thrombectomy, tumor embolization was diagnosed during a period of hypotension based on transesophageal echocardiographic finding of new thrombus within the right atrium. This prompted sternotomy, CPB, and pulmonary artery embolectomy. The patient survived this embolization event and has a complete response to systemic therapy 9 months postoperatively. This case serves as the framework for a discussion on management considerations surrounding intraoperative embolization during IVC thrombectomy.